Hydrosedimentological studies in the Paciencia Dam, Southeastern Brazil (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The utilization of dams for many purposes, such as water supply, navigation, flood control, irrigation, storage of water and generation of electricity, among others, solves several problems but unfortunately creates many others. Water management is not a simple task, and the presence of dams generates social, physical, chemical, biological and environmental consequences. Among these severe impacts associated to the implantation and operation of dams, the issues related to the transported and deposited sediments are very significant, although many times hard to evaluate. The objective of this paper is to present the results of studies performed close to the dam of a small hydro power plant located in the Paraibuna River, in the southeast part of Brazil. A grain size analysis of the sediments and its chemical characterization were evaluated before and after a bottom discharge. Two bathymetric surveys in a section of 1.6 km upstream the dam were also performed, one just before and other just after the bottom discharge, in order to evaluate its influence in the bathymetry of the river. The results showed that after the bottom discharge, the amount of muddy sediments upstream the dam became smaller. Regarding to the heavy metal content, the bottom sediments collected upstream and downstream the dam presented, in several samples, values higher than the threshold above which a probable adverse effect on the biota is expected, in particular for cadmium, chromium and zinc, in order of importance.
Keywords: Sedimentation, Bottom Discharge, Environmental Evaluation, Paciência Dam, Brazil.